2016
DOI: 10.3389/fnhum.2016.00183
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Regulation Following fMRI-Neurofeedback without Instructed Strategies

Abstract: Within the field of functional magnetic resonance imaging (fMRI) neurofeedback, most studies provide subjects with instructions or suggest strategies to regulate a particular brain area, while other neuro-/biofeedback approaches often do not. This study is the first to investigate the hypothesis that subjects are able to utilize fMRI neurofeedback to learn to differentially modulate the fMRI signal from the bilateral amygdala congruent with the prescribed regulation direction without an instructed or suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 41 publications
1
65
0
2
Order By: Relevance
“…To fill this knowledge gap, we adapted an rtfMRI amygdala neurofeedback protocol established by our group (Paret et al, 2014). Previous research has shown that amygdala regulation with neurofeedback is feasible (Br€ uhl et al, 2014;Marxen et al, 2016;Paret et al, 2014;Zotev et al, 2011) and can improve the regulation of emotions in patients suffering from affective dysregulation (Gerin et al, 2016;Keynan et al, 2016;Nicholson et al, 2016;Paret et al, 2016a;Young et al, 2014Young et al, , 2017aYoung et al, , 2017bYuan et al, 2014). Emotion regulation is associated with specific control of amygdala activation (Buhle et al, 2013) and involves the dlPFC (Kalisch, 2009), whereas the monitoring of affect involves the ACC and medial PFC (Etkin et al, 2011).…”
mentioning
confidence: 99%
“…To fill this knowledge gap, we adapted an rtfMRI amygdala neurofeedback protocol established by our group (Paret et al, 2014). Previous research has shown that amygdala regulation with neurofeedback is feasible (Br€ uhl et al, 2014;Marxen et al, 2016;Paret et al, 2014;Zotev et al, 2011) and can improve the regulation of emotions in patients suffering from affective dysregulation (Gerin et al, 2016;Keynan et al, 2016;Nicholson et al, 2016;Paret et al, 2016a;Young et al, 2014Young et al, , 2017aYoung et al, , 2017bYuan et al, 2014). Emotion regulation is associated with specific control of amygdala activation (Buhle et al, 2013) and involves the dlPFC (Kalisch, 2009), whereas the monitoring of affect involves the ACC and medial PFC (Etkin et al, 2011).…”
mentioning
confidence: 99%
“…To test whether a subject's ability to directly modulate target brain regions improves task performance, investigators can present sensory feedback that scales with the amplitude of brain activity. The use of this technique has revealed that subjects can learn to regulate the activity of subcortical areas, including the amygdala and basal ganglia, and extended areas of the limbic system, including the insula and parahippocampus . Interestingly, participants can also learn to modulate the primary sensory motor cortex (primary motor area, premotor cortex, and supplementary motor area) as well as higher‐order areas, including the anterior cingulate cortex, ventral tegmental area, frontal and parietal cognitive control areas, anterior midcingulate cortex, and frontal cortex .…”
Section: Neurofeedback For Cognition: a Primermentioning
confidence: 99%
“…Studies demonstrate that, even when explicit instructions or strategies are not provided, subjects can search for an effective strategy to self‐regulate functional brain dynamics . Such open‐ended experimentation is especially powerful for investigating how subjects employ unique strategies to modulate brain dynamics . Indeed, it is of interest to explicitly map individual variability in the chosen control strategy to the subjects' ability to modulate target brain areas.…”
Section: Neurofeedback For Cognition: a Primermentioning
confidence: 99%
See 2 more Smart Citations